Strategi Diferensiasi: Mencapai Keunggulan Kompetitif yang Sustainable - Maria Widyastuti (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2011)
Differentation is an effort to descript spesifik characteristic(uniqueness) of aproduct, with the uniqueness owned by a product, so the consumer will be able torecognize this product easily so consumer will be. Because of the main focus iscustomer, then this strategy must give satisfaction to consumer. Differentationstrategy is one of three excellent competitiveness offered by Portes through hisgeneric strategy, leadership of total cost differentiation and focus. To increasedifferentiation can be done by two way implement the existing value activity to bemore unique or the company reset the value of chain. To be successcfull inimplementing both.